Strategi Pemasaran Menggunakan Sistem Konsinyasi Terhadap Produk Stik Kelor Desa Tambu - Ikbal Pratama M. Supu; Muhammad Din; Maskuri Sutomo (Universitas 45 Surabaya, 2023)
Business actors have various ways to market their products so that these products can be found by consumers. With various theories about marketing strategy carried out by business actors, and demanded to balance their business with current progress, especially in terms of sales. One of the policies regarding the strategy in selling products is that it can be done by selling (consignation). Consignation or commonly used to be used by selling is a sale by the way the owner entrusts the goods to other parties to be sold at the price and conditions that have been set in the agreement. In this case we use a consignation sales system in marketing moringa stick products in tambu village. By using the FGD method, observation and interviews in determining the place of marketing carried out. Hopefully in this way the tambu village business group can be helped in marketing the products.